Gen Z's Coffee Culture: How TikTok eWOM and Brand Image Build Trust and Shape Preference for Local Coffee Shops - Warren Warren; Patricia Idella Saputra; Agustinus Nugroho (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the role of electronic word of mouth (eWOM) on TikTok and brand image in shaping Generation Z's brand preference for local coffee shops, with brand trust as a mediating variable. The growth of coffee consumption culture among Gen Z and the increasing use of TikTok as a digital platform have changed the way consumers form perceptions and choose brands. However, research integrating eWOM, brand image, brand trust, and brand preference in the context of local coffee shops is still limited. This study fills this gap by analyzing the direct and indirect relationships between variables. A quantitative approach was used through a survey method with a purposive sampling technique on a minimum of 130 Generation Z respondents in Surabaya who actively use TikTok and have visited local coffee shops. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that eWOM and brand image have a positive and significant effect on brand trust, and eWOM, brand image, and brand trust have a significant effect on brand preference. In addition, brand trust is proven to partially mediate the relationship between eWOM and brand preference, as well as between brand image and brand preference. Among all variables, eWOM has the most dominant influence on brand preference. This finding indicates that local coffee shops need to integrate TikTok-based eWOM strategies with consistent brand image building to strengthen brand trust and increase Gen Z consumer preference. Keywords: eWOM; TikTok; brand trust; brand image; brand preference; Gen Z; local coffee shops.